EFSUMB Guidelines on Multiparametric Ultrasound Thyroid Nodule Evaluation: PART II - Cantisani, Vito; Radzina, Maija; Dietrich, Christoph F.; Jenssen, Christian; Prosch, Helmut; Appelbaum, Liat; Barr, Richard G; Bhatia, Kunwar S S; Dighe, Manjiri; Durante, Cosimo; Fresilli, Daniele; Grani, Giorgio; Harvey, Chris; HUANG, Pintong; Ivanac, Gordana; Lim, Adrian; Ozbek, S Sureyya; Secil, mustafa; Todsen, Tobias; Trimboli, Pierpaolo (Ultraschall in der Medizin - European Journal of Ultrasound)
Thyroid nodules are common incidental findings but only a small proportion of cases are malignant (4-6.5%) or symptomatic. Numerous follow-up examinations and invasive diagnostic procedures, such as fine-needle aspiration, fine-needle biopsies, and thyroidectomies, are performed, leading to potentially costly and time-consuming diagnostic procedures and overtreatment. Most experts and scientific societies (EFSUMB, WFUMB...) encourage the use of multiparametric ultrasound evaluation to improve the thyroid nodule characterization thanks also to the continuous technological developments with different ultrasound software (Microvascular flow imaging, Elastosonography...), contrast media (CEUS) and artificial intelligence (AI). Therefore, the recognition and proper use of new multiparametric ultrasound features of thyroid nodules are essential to minimize unnecessary interventions and guide appropriate treatments, also stimulating their use in routine clinical practice, which is the aim of our guideline. In addition, we analyze the use of MPUS in some emblematic thyroid scenarios such as cytologically indeterminate nodule, multinodular goiter and extrathyroidal extension of the malignant nodule and the usefulness of MPUS as a guide to thyroid biopsy/aspiration and in the staging of cervical lymph nodes. For each question, recommendations based on the level of evidence of the published literature and on the EFSUMB expert group's consensus are given.